BERAT BADAN BAYI BARU LAHIR PADA IBU DENGAN HIPERTENSI DI RUMAH SAKIT DAERAH GUNUNG JATI KOTA CIREBON - Dea Nurtika Fajri; Ani Nurhaeni; Sumarni (Jurnal Kesehatan Mahardika, 2019)
Hypertension in pregnancy is one of the three highest causes of maternal mortality and mobility. High blood pressure of pregnant women (hypertension) can result in impaired intrauterine fetal growth which will certainly have an impact on birth weight. The purpose of this study was to determine the description of newborn weight in mothers with hypertension in the ​​Gunung Jati Hospital Cirebon in 2019. The type of research used was descriptive method. The population used in this study were mothers with hypertension in Gunung Jati Hospital as many as 71 people with a sample of 71 respondents. The instrument used in this study used a checklist sheet using secondary from parturition book for the Gunung Jati Regional Hospital in January-March 2019. The results showed the classification of hypertension in maternal women due to gestational hypertension was 28 (39.4%) and newborn birth weight for mothers with hypertension weighing 2,500-4,000 grams as much as 50 (65.0%). For this reason, during pregnancy, pregnant women are expected to know about the symptoms of hypertension that occur during pregnancy, so that they can be prevented as early as possible by resting, carrying out regular monthly checks and taking a healthy lifestyle.